2009
DOI: 10.1073/pnas.0807708106
|View full text |Cite
|
Sign up to set email alerts
|

Learning-related postburst afterhyperpolarization reduction in CA1 pyramidal neurons is mediated by protein kinase A

Abstract: Learning-related reductions of the postburst afterhyperpolarization (AHP) in hippocampal pyramidal neurons have been shown ex vivo, after trace eyeblink conditioning. The AHP is also reduced by many neuromodulators, such as norepinephrine, via activation of protein kinases. Trace eyeblink conditioning, like other hippocampus-dependent tasks, relies on protein synthesis for consolidating the learned memory. Protein kinase A (PKA) has been shown to be a key contributor for protein synthesis via the cAMP-response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 73 publications
1
64
0
Order By: Relevance
“…Learning-dependent reductions in mAHP and sAHP have been reported in hippocampus following acquisition of trace eyeblink conditioning (Matthews et al, 2009). In addition, NE has been shown to reduce both currents via PKA-dependent phosphorylation (Pedarzani and Storm, 1995;Lancaster et al, 2006;Oh et al, 2009). Learning-dependent AHP plasticity in multitrial tasks has been shown to be PKA-but not PKC-dependent (Oh et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Learning-dependent reductions in mAHP and sAHP have been reported in hippocampus following acquisition of trace eyeblink conditioning (Matthews et al, 2009). In addition, NE has been shown to reduce both currents via PKA-dependent phosphorylation (Pedarzani and Storm, 1995;Lancaster et al, 2006;Oh et al, 2009). Learning-dependent AHP plasticity in multitrial tasks has been shown to be PKA-but not PKC-dependent (Oh et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, NE has been shown to reduce both currents via PKA-dependent phosphorylation (Pedarzani and Storm, 1995;Lancaster et al, 2006;Oh et al, 2009). Learning-dependent AHP plasticity in multitrial tasks has been shown to be PKA-but not PKC-dependent (Oh et al, 2009). Learning-dependent AHP plasticity occurred with different time courses in dorsal and ventral CA1.…”
Section: Discussionmentioning
confidence: 96%
“…This has been shown in detail with regard to serotonin (see, for example, Joëls et al, 1991;Laaris et al, 1999;Fairchild et al, 2003; for reviews, see Joëls et al, 2007;Haj-Dahmane and Shen, 2011), noradrenaline, and, to a lesser extent, CRH (Gallagher et al, 2008). For instance, noradrenaline (acting via ␤-receptors) targets the AHP (Madison and Nicoll, 1982;Faber and Sah, 2005;Oh et al, 2009), GluA2 subunit trafficking (Liu et al, 2010), and (maintenance of) LTP (Thomas et al, 1996;Straube and Frey, 2003;Gelinas and Nguyen, 2005), thereby mimicking effects described for corticosteroids. These common endpoints form potential platforms for interaction between various stress mediators .…”
Section: In Search Of Multiple Dimensionsmentioning
confidence: 99%
“…The first PKA wave occurs immediately after training and the second after 3-6 h. Both waves of PKA activity might be important to induce CREB-mediated gene transcription (Ahi et al 2004;Sindreu et al 2007). Next to regulating gene transcription for LTM formation, PKA has also been implicated in synaptic tagging (Young et al 2006;Moncada et al 2011) and long-term reduction of the slow afterhyperpolarization (AHP), which regulates neuronal firing (Oh et al 2009). Further, PKA activity is required for the behavioral counterpart of synaptic tagging (Moncada et al 2011).…”
Section: Pkamentioning
confidence: 99%